Application of situational simulation based on the Mini-CEX and DOPS rating scales in urology clinical training - Xu, Ben; Zhang, Jia-en; Ye, Lin; Yuan, Chang-wei (Frontiers in Medicine, 2024)
Objectives: To investigate the application effect of scenario simulation teaching based on Mini-CEX and DOPS rating scale in the teaching of urology clinical apprenticeship. Materials and Methods: Thirty-two students of the class of 2015-2017 who underwent traineeship in the department of Urology of our hospital were selected and divided into a research group and a routine group; routine teaching was implemented for the trainees in the control group, and situational simulation teaching based on the Mini-CEX and DOPS scoring scales was implemented for the trainees in the research group to compare the Mini-CEX and DOPS scores and student satisfaction at the time of admission to the department and at the time of discharge from the department of the trainees of the two groups. Results: At the time of admission, there was no statistically significant difference between the Mini-CEX scores and DOPS scores of the two groups of trainees (p > 0.05), and at the time of discharge, the Mini-CEX and DOPS scores of the trainees in the study group were (53.21 ± 4.52) and (81.23 ± 3.57), respectively, which were significantly higher than those of the conventional group (p < 0.001); and the trainees in the study group's satisfaction with teaching was (20.11 ± 0.001). satisfaction score was (20.11±2.31), which was significantly higher than that of the conventional group (p <0.001). Conclusions: The implementation of scenario simulation teaching based on Mini-CEX and DOPS rating scale in the teaching of urology clinical traineeship can significantly improve the trainees' clinical operation skills, and the trainees' satisfaction with the teaching mode is high.